Efektivitas baby massage terhadap peningkatan kualitas tidur bayi - Adhiestiani, Ni Made Egar; Purnamayanthi, Pande Putu Indah; Ekajayanti, Pande Putu Novi (Holistik Jurnal Kesehatan, 2025)
Background: Babies need 12-14 hours of sleep every day, including naps to ensure their bodies and brains develop properly and normally. One way to maintain a baby's health is to give them a baby massage. Purpose: To determine the effectiveness of baby massage in improving the quality of baby sleep. Method: Quantitative research with a quasi-experimental posttest only control design. The number of samples was 32 people determined by purposive sampling technique. Measurement of sleep quality using a questionnaire referring to the Brief Infant Screening Questionnaire (BISQ) and the data analysis used was the Mann Whitney U Test. Results: Based on the Mann Whitney U Test, a p value of 0.02 (<0.05) was obtained, which means that there is a significant difference in the quality of baby sleep after being given a baby massage between the intervention group and the control group. Conclusion: Baby massage is effective in improving the quality of baby sleep, so it is hoped that health workers will be able to provide education to the community, especially parents, so that they can improve the quality of baby sleep, as well as optimal baby growth and development.   Keywords: Baby; Massage; Sleep Quality.   Pendahuluan: Bayi membutuhkan 12-14 jam tidur setiap hari, termasuk tidur siang untuk memastikan bahwa tubuh dan otak mereka berkembang dengan baik dan normal. Salah satu cara untuk menjaga kesehatan bayi adalah dengan memberikan baby massage (pemijatan). Tujuan: Untuk mengetahui efektivitas baby massage terhadap peningkatan kualitas tidur bayi. Metode: Penelitian kuantitatif dengan desain quasi experimental post-test only control design. Besar sampel sebanyak 32 partisipan yang ditentukan dengan teknik purposive sampling. Pengukuran kualitas tidur menggunakan kuesioner yang mengacu pada Brief Infant Screening Questionnaire (BISQ) dan analisis data yang digunakan adalah Mann Whitney U Test. Hasil: Berdasarkan uji Mann Whitney U Test, diperoleh nilai p 0.02 (<0.05), berarti terdapat perbedaan yang signifikan kualitas tidur bayi setelah diberikan baby massage antara kelompok intervensi dengan kontrol. Simpulan: Baby massage efektif dalam meningkatkan kualitas tidur bayi, sehingga tenaga kesehatan diharapkan mampu memberikan edukasi kepada masyarakat, khususnya orang tua agar dapat meningkatkan kualitas tidur bayi, pertumbuhan, dan perkembangan bayi menjadi optimal.   Kata Kunci: Baby Massage; Bayi; Kualitas Tidur.